DNA methylation changes involved in the tumor increase in F2 males born to gestationally arsenite‐exposed F1 male mice. Issue 8 (25th July 2019) - Okamura, Kazuyuki; Nakabayashi, Kazuhiko; Kawai, Tomoko; Suzuki, Takehiro; Sano, Tomoharu; Hata, Kenichiro; Nohara, Keiko
Abstract: Multigenerational adverse effects from the environment such as nutrition and chemicals are among important concerns in environmental health issues. Previously, we have found that arsenite exposure of only F0 females during their pregnancy increases hepatic tumors in the F2 males in C3H mice. In the current study, we investigated the association of DNA methylation with the hepatic tumor increase in the F2 males of the arsenite group. Reduced‐representation bisulfite sequencing analysis newly identified that DNA methylation levels of regions around the transcriptional start sites of Tmem54 and Cd74 were decreased and the expression of these genes were significantly increased in the hepatic tumors of F2 males of the arsenite group. The associations between DNA methylation in these regions and gene expression changes were confirmed by treatment of murine hepatoma cell lines and hepatic stellate cell line with 5‐aza‐2′‐deoxycytidine. Overexpression of Cd74 in Hepa1c1c7 cells increased Trib3 expression and suppressed the expression of tumor suppressor genes Id3 and Atoh8 . Human database analysis using the Cancer Genome Atlas indicated that TMEM54, CD74, and TRIB3 were significantly increased and that ATOH8 was decreased in hepatocellular carcinoma. The data also showed that high expression of TMEM54 and TRIB3 and low expression of ATOH8 were associated with poor survival. These results suggested that an increase in Tmem54 and Cd74 expression via DNA methylation reduction was involved in the tumor increase in the F2 male offspring by gestational arsenite exposure of F0 females. This study also suggested that genes downstream of Cd74 were involved in tumorigenesis. Abstract : The present study proposes that an increase in Tmem54 and Cd74 expression via DNA methylation reduction was involved in the tumor increase in the F2 male offspring due to gestational arsenite exposure of F0 females.